Sosialisasi Panduan Penulisan Artikel Ilmiah Menggunakan Pendekatan Kualitatif - Henri Henri; A. Muh. Ali; Syakia Muflihat; Nurul Jamiah Sidiq; Sakmawati Sakmawati (Jurnal Hasil-Hasil Pengabdian dan Pemberdayaan Masyarakat, 2024)
Community service activities in the form of socialization of scientific article writing guidelines aim to improve participants' skills in preparing scientific articles. 79 participants from various departments attended the workshop. The materials covered include structuring scientific articles, selecting topics, objectives, methods, and discussion, and using reference manager tools. The implementation methods included theoretical presentations, interactive discussions, and evaluation. Evaluation results showed that 85% of participants found the material presented easy to understand and were satisfied with the activity. This event is expected to encourage the participant’s academic productivity and improve the quality of their scientific publications.